Historical Analysis of Criminalizing Homosexual Relationships in Nigeria: A Historical Approach - Mamudu, Ganni Kashetu (Abdul Media Literasi, 2024)
This paper aims basically at examining the menace and the criminalization of homo-sexual relationships in Nigerian society. Gay and lesbian couples are categorized as same-sex relationships. Though they are not easy to identify, they possess peculiar traits which set them apart from ordinary persons. Their activities are generally condemned by most countries on religious and moral grounds. This work has succinctly examined the various causes of homosexuality and its effects on our society. The study adopted a multi-disciplinary approach in its analysis. It employs a historical, expository, interpretative, and analytical method. A secondary source was extensively used in the course of this study. It also evaluates the role or views of different sections in society as regards the activities of homosexuality in our society. Besides, the concepts and analytical tools of economists, sociologists, and theologists were employed throughout the analysis. This ensured that the paradigmatic tool that was used melded perfectly into the overall body of the paper. This was adopted because of the historical nature of the study. It was discovered that homosexuality is largely due to the environment in which one is raised. In other words, homosexuality is induced by a disordered environment. People equally engaged in homosexuality as a result of freedom of association. They feel it is one of their fundamental human rights. To some of the practitioners, it is more economical. There is no fear of pregnancy and some other related expenses involved in a normal relationship.